A Needle in a Haystack: Looking for an Early Modern Peasant Who Travelled from Spain to America - Albiez Wieck, Sarah (2022)
Seventeenth-century travel accounts written by ordinary people are a rarity. In this article, we analyze the unusual travel report by Gregorio de Robles, a Castilian peasant (labrador) who travelled several European empires in Western Europe and America at the end of the seventeenth and the beginning of the eighteenth centuries. The approach we offer is that of a global microhistory. The aim of this article is mainly methodological: we try to delineate the methodological steps we had to undertake to trace Robles in the sources. Looking for an early modern peasant traveler is comparable to searching for a needle in a haystack, but we argue that this endeavor is worthwhile because Robles offers a unique perspective on how ordinary people traveled in early modern times and on imperial frontier zones. We show that his convivial ties and the places he mentions were key elements in the methodology.